2019
DOI: 10.3390/nu11122902
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity in Mice Exacerbates the Allergic Inflammatory Response in the Airways of Male Offspring

Abstract: It was previously demonstrated that non-allergen-sensitized rodents born to mothers exposed to a high-fat diet (HFD) spontaneously develop lower respiratory compliance and higher respiratory resistance. In the present study, we sought to determine if mice born to mothers consuming HFD would exhibit changes in inflammatory response and lung remodeling when subjected to ovalbumin (OVA) sensitization/challenge in adult life. Mice born to dams consuming either HFD or standard chow had increased bronchoalveolar lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In the first stage of the KD pathological process, neutrophil-dominated immune cells mediate necrotizing vasculitis leading to full-thickness damage to the vessel wall [15,18]. Furthermore, animal study has demonstrated that maternal obesity exacerbated the infiltration of neutrophil in inflammatory response in the airways of male offspring [46]. Collectively, our findings suggest that maternal obesity may affect the long-term immune response and exacerbate KD-like vasculitis in male offspring mice through G-CSF.…”
Section: Discussionmentioning
confidence: 60%
“…In the first stage of the KD pathological process, neutrophil-dominated immune cells mediate necrotizing vasculitis leading to full-thickness damage to the vessel wall [15,18]. Furthermore, animal study has demonstrated that maternal obesity exacerbated the infiltration of neutrophil in inflammatory response in the airways of male offspring [46]. Collectively, our findings suggest that maternal obesity may affect the long-term immune response and exacerbate KD-like vasculitis in male offspring mice through G-CSF.…”
Section: Discussionmentioning
confidence: 60%
“…The higher risk of allergic reactions in children of obese mothers seems to depend on the increased production of inflammatory cytokines induced by excess adipose tissue. Such changes are likely to result from long-lasting changes in miR-155 and miR-133b expression [39]. Secondly, environmental factors: different studies suggest that exposure to air pollution and passive tobacco smoking are independent risk factors for the development of both asthma [40,41] and obesity in children [42,43].…”
Section: Obesity and Asthmamentioning
confidence: 99%
“…Excess fat mass in the chest wall and abdomen reduces the functional residual capacity of the lung (FRC) [37]. It is also associated with both reduced forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) [37][38][39][40][41][42][43][44][45]. Low tidal volume breaths due to thoracic and abdominal fat excess lead to low lung volumes [46], causing alveolar hypoventilation and an increase in airway resistance [47].…”
Section: Obesity and Asthmamentioning
confidence: 99%
“…HFD was administered before mating and kept throughout pregnancy and lactation in a model of pediatric obese asthma. Then, offspring were sensitized to OVA at 6 weeks of age ( E-Lacerda et al, 2019 ). The results showed that the progeny of the obese mice displayed exacerbated responses and intense lung remodeling in the OVA-induced asthma model, which are featured by elevated IL-4, IL-13, TNF-α, TGF-β levels, leukocyte infiltration and collagen deposition.…”
Section: Immune Responses In the Different Obesity-related Asthma Mou...mentioning
confidence: 99%